Juan Muñoz the politics of silence - Stuart-Smith, Mark 1958- (Peter Lang, 2024)
«Through marvelously attentive case studies of a handful of works, some canonical, others obscure, Mark Stuart-Smith provides the most thorough exploration so far of Juan Muñoz’s mesmerizing and haunted world. He inhabits the works, analyzing their mechanisms, materialities and drama, while at the same time connecting them to histories of politics, art and thought of great urgency to Muñoz and no less urgency now. This book has much to say not only about the forces and voices of silence but also about Muñoz’s extraordinary struggle to make art that could hold its own against the fascinations of image and spectacle.»(Michael Brenson, author of David Smith: The Art and Life of a Transformational Sculptor (2022))The spectacular international success of the Spanish sculptor Juan Muñoz has tended to encourage a critical framing of the artist’s work within narratives of global postmodernist innovation. This book, the first in-depth study of the central idea of silence in Muñoz’s work, aims to position him more clearly within his historical moment, by reading his work against the silences of Spanish politics and culture in post-Civil War Spain.Drawing on a wealth of documents, beginning with Muñoz’s student notebooks, the book shows how silence and memory defined and shaped his art. A range of methodologies from within Muñoz’s own intellectual horizon is applied to explore a progression from the implied silences of his sculptural installations to the literal sounds and silences of his first radio piece. Muñoz’s silencing strategies are analysed across different mediums, both visual and verbal, to show how his art probes and reanimates the uncanny memory of Spain’s traumatic past
Keywords: Muñoz, Juan -- 1953-2001; Stille -- Motiv; Installation -- Kunst; Objektkunst; Hardcover, Softcover / Sprachwissenschaft, Literaturwissenschaft/Romanische Sprachwissenschaft, Literaturwissenschaft